ANALISA MANFAAT PEMASANGAN CAPACITOR BANK UNTUK MEMPERBAIKI FAKTOR DAYA DAN MENGURANGI KERUGIAN DAYA DAN ENERGI LISTRIK DI POLITEKNIK PENERBANGAN SURABAYA - Hartono Hartono; Heri Sudarmadji; Slamet Hariyadi; Rifdian IS; Siti Julaihah; M. Indra Martadinata (Jurnal Penelitian)
Electric power quality problems include line losses, voltage drops, and the amount of inductive reactive power consumed at load so the power factor is low. Power factor improvement in Politeknik Penerbangan Surabaya electrical system to 0,99 is expected to improve electric power quality by installing a setcapacitorsitor called Capacitor Banks that supply capacitive reactive power. Another benefit is that reduces the load on transformer Poltekbang Surabaya which is now approaching full load. To be able to repair the electric power supply is necessary to measure and calculate the inductive reactive power which can be compensated with witcapacitiveie reactive power by Capacitor Bank. After calculating the capacitor bank value, the location of the capacitor bank installation is then determined so that power improvements can be carried out effectively, The result shows that the compensation needed to improve the power factor on Poltekbang Surabaya is 300 kVAR divided into 5steps, each step requires a 50 kVAR capacitor